Vocational School Level Learning Model for Work Readiness: A Systematic Literature Review - Affandi, Lukman; Indriayu, Mintasih; Totalia, Salman Alfarisy (Mitra Edukasi dan Publikasi, 2025)
The mismatch between vocational school graduates' competencies and industry needs remains a major cause of youth unemployment. This research aims to provide a comparative view of the learning models used at the vocational school level to prepare students to have a work readiness attitude t aligned with 21st-century industry demands. This research is a systematic review of literature that explains a connection between learning models at the vocational school level to prepare students' work attitudes according to industry demands. There are seven learning models from 14 articles obtained in the research. This research links the vocational school level learning model, 21st century skills to students' work readiness according to industry demand. The research concludes that the Learning and Training Within Industry, Teaching Factory, Blended Learning, Project Based Learning, Problem Based Learning, Lean Based Learning, and Work Based Learning models can meet the criteria for incorporating 21st century skills to increase the work readiness of vocational school graduates so they can be absorbed in industry.